Maxim Violation Done by Emily in Emily in Paris Movie - Dewi, Ni Made Permata; Candra, Komang Dian Puspita; Ayomi, Putu Nur (Journal of Language and Applied Linguistics, 2023)
This article investigates the Maxim Violation analysis employed by Emily, the main character in the movie. The data was taken from Emily in Paris Season 1 Movie. The goal of this research is to discover different types of maxim violations and figure out what motivates the main character to violate the maxim. The data was gathered using the observation approach, which contained steps such as downloading and observing the data, finding the script, and writing notes for the discussion that showed the violation of the maxim. The data were analyzed using a qualitative methodology. The study was comprehended using theory from Grice's maxim violation theory (1975). The results of the analysis of selected dialogue in the movie indicate that there are 28 data points in the film that include Maxim Violation. Quantity, quality, relevance, and manner can all be characterized as types of maxim violations. The reason that motivates the main character to violate the maxim was discovered in this film, which is supported by the context of the situation that occurs in Emily in Paris season 1 movie.